Poverty-associated emerging infection of Cystic Echinococcosis in population of Northern Pakistan: A hospital based study - Khan, A.; Ahmed, H.; Simsek, S.; Gondal, M. A.; Afzal, M. S.; Irum, S.; Yayi, G. (Malaysian Soc Parasitology Tropical Medicine, 2019)
Cystic Echinococcosis (CE) is one of the most important zoonotic parasitic diseases in human, livestock, and wildlife globally. The prevalence of CE depends upon human behavioral risk factors, the diversity and ecology of animal host interactions and the genetic diversity within Echinococcus species which differ in their zoonotic potential and pathogenicity. It is a neglected, economic and socio-cultural problem in Pakistan. The available data about the incidence of CE is very limited and no extensive study has been reported in Pakistan. The current study was aimed to analyze the hospital reported cases of CE and the associated risk factors related to the incidence of CE. The hospital-based data of CE for the time period of January 2012-December 2017 was collected from Islamabad, Rawalpindi and Peshawar. The data covered demographic characteristics including age, gender, and cyst localization of infected individuals and socioeconomic determinants. The data was analyzed based upon different risk factors along with the different socioeconomic parameters that has an important impact on the distribution of disease. A total of 228 cases were presented in the selected hospitals of different cities during the study period. Out of total 228 patients, 59.21% were males and 40.78% were females (P<0.001). Most infections have been recorded in young adults (>20-30) showing 22.8% of total infected individuals followed by children (0-10) showing 10.5% (n=24), respectively (P<0.001). Liver was the most vulnerable organ (58.77%, n=134) followed by lungs (14.47%, n=33) (P<0.001). The infection was higher among rural communities (84.2%) than urban (12.8%) (P<0.001). Socioeconomic and demographic factors had an important impact on the intensity of disease (P<0.001). The occurrence of cases in children and young adults was an important finding as it indicated an active transmission of the parasite in Pakistan along with the poverty index. Emergence of echinococcosis in Pakistan showed that emerging health issues in Pakistan could bring the disease to limelight for future research. This finding, together with the fact that 1 hospital reported 214 cases over 6 years underlines the need for a program for prevention/control of this disease in Pakistan. The timely measure needs to be taken to hamper the disease development and establishment. In order to control the disease, complete surveillance should be done which in turn weighs down the disease progress.
Keywords: Praziquantel Treatment; Hydatid-Disease; Granulosus; Alveolar; Province